Edward Anseele ter ere. - Crommen, Gaston; Huysmans, Camille; de Brouckère, Louis (Gent : De Vlam, 1948)
Bibliotheek Camille Huysmans
Archief Guy VanschoenbeekArchief PMB Oost-VlaanderenArchief Christian Leire
Nederlands
Monografie
Keywords: socialistische arbeidersbeweging; België